1989
DOI: 10.2172/6360676
|View full text |Cite
|
Sign up to set email alerts
|

A study of post-thermal recovery of the macroinvertebrate community of Four Mile Creek, June 1985--September 1987. [Savannah River Plant]

Abstract: This report was prepared as an account of work sponsored by an agency of the United States Government, Neither the United States Government nor any agency thereof, nor any of their employees, makes any warranty, express or implied, or assumes any legal liability or responsibility for the accuracy, completeness, or usefulness of any information, apparatus, product, or process disclosed, or represents that its use would not infringe privately owned rights. Refer-_.e_ h_.reinto any specific commercial product, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

1993
1993
2006
2006

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 0 publications
2
8
0
Order By: Relevance
“…Similarly, conditions immediately below the APS were extremely poor in fall 2002. However, chemical and biological conditions downstream Overall, our results are consistent with numerous studies documenting negative impacts of mining-related discharges (e.g., Cain et al, 2000;Soucek et al, 2001a;DeNicola & Stapleton, 2002) and thermal pollution (e.g., Poff & Matthews, 1986;Lauritsen & Starkel, 1989;Wellborn & Robinson, 1996) on water quality and aquatic organisms. The dominant effect of these stressors is to reduce invertebrate numbers, diversity, and richness to a few tolerant taxa (Cherry et al, 2001;DeNicola & Stapleton, 2002;Schmidt et al, 2002).…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, conditions immediately below the APS were extremely poor in fall 2002. However, chemical and biological conditions downstream Overall, our results are consistent with numerous studies documenting negative impacts of mining-related discharges (e.g., Cain et al, 2000;Soucek et al, 2001a;DeNicola & Stapleton, 2002) and thermal pollution (e.g., Poff & Matthews, 1986;Lauritsen & Starkel, 1989;Wellborn & Robinson, 1996) on water quality and aquatic organisms. The dominant effect of these stressors is to reduce invertebrate numbers, diversity, and richness to a few tolerant taxa (Cherry et al, 2001;DeNicola & Stapleton, 2002;Schmidt et al, 2002).…”
Section: Discussionsupporting
confidence: 91%
“…However, macroinvertebrates also were collected from leaf bags, artificial snags, macrophytes, natural substrates, and drift at some stations. Details of sampling methods can be found in Specht et al (1984), , , Lauritsen and Starkel (1989), and . Most of the data in this summary is from the 1984-1985 sampling period because fewer stations were sampled in the other years.…”
Section: Methodsmentioning
confidence: 99%
“…Because C Reactor, which discharged to Fourmile Branch, was placed on cold standby in June 1985, these data primarily represent the macroinvertebrate community that existed when C Reactor was operating at full power; however, the data also document early recovery of thermal stations between June and September 1985. After C Reactor shut down in June 1985, Lauritsen and Starkel (1989) .…”
Section: Section 53-founnile Branchmentioning
confidence: 99%
“…Gladden (1988) concluded that the macroinvertebrate community in Fourmile Branch was similar to the trophic structure of macroinvertebrate communities in upper Pen Branch and Meyers Branch, both of which have not been adversely affected by SRS operations. Lauritsen et al (1989) examined macroinvertebrates in Fourmile Branch between June 1985 and September 1987 as part of a larger study of SRS streams. They found that following the shut down of C-Reactor, recolonization of the stream by macroinvertebrates began within a month and proceeded rapidly.…”
Section: Macroinvertebratesmentioning
confidence: 99%